1998
DOI: 10.1111/j.1365-2338.1998.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, immunological and molecular methods suitable for commercial detection and quantification of the blackleg pathogen, Erwinia carotovora subsp. atroseptica, on seed potato tubers: a review

Abstract: Contamination of seed potato tubers by Erwinia carotovora subsp. atroseptica is widespread with the bacteria usually sited superficially in lenticels and suberized wounds. As seed contamination level is related to blackleg incidence, seed health is best assessed by determining the number of cells of E. c. atroseptica per mL of tuber‐peel extract. The relative specificity, sensitivity and ease of use of four recently developed microbiological, immunological and molecular methods to detect and/or quantify tuber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…To remove adhering soil and other debris and to minimize the competition in culture by non‐target microbes, tuber washing is often regarded as an important pre‐PCR step in detection of soft rot erwiniae. All the published PCR or ELISA based detection of soft rot and blackleg in potatoes (Bång, 1989; Hyman et al., 1997; Pérombelon et al., 1998; Hyman et al., 2000; De Boer, 2002; Hélias et al., 1998) included tuber washing. However, washing could be the main source of tuber‐tuber surface contamination if a decaying tuber is washed and mixed with healthy ones as demonstrated by the results of this study (Table 2) where bulk washing of 20 healthy tubers with one rotten or decaying (advanced soft rot) tuber included caused a surface contamination or false positives on up to 91% of healthy tubers suggesting that there could be high risk of obtaining false positive or over estimated PCR results if tubers are washed in bulk (healthy and decaying tuber mixed together) and not individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove adhering soil and other debris and to minimize the competition in culture by non‐target microbes, tuber washing is often regarded as an important pre‐PCR step in detection of soft rot erwiniae. All the published PCR or ELISA based detection of soft rot and blackleg in potatoes (Bång, 1989; Hyman et al., 1997; Pérombelon et al., 1998; Hyman et al., 2000; De Boer, 2002; Hélias et al., 1998) included tuber washing. However, washing could be the main source of tuber‐tuber surface contamination if a decaying tuber is washed and mixed with healthy ones as demonstrated by the results of this study (Table 2) where bulk washing of 20 healthy tubers with one rotten or decaying (advanced soft rot) tuber included caused a surface contamination or false positives on up to 91% of healthy tubers suggesting that there could be high risk of obtaining false positive or over estimated PCR results if tubers are washed in bulk (healthy and decaying tuber mixed together) and not individually.…”
Section: Discussionmentioning
confidence: 99%
“…There was almost no case where tubers tested positive in stolon end sample and tested negative in tuber peel samples, whereas the converse was true. All the published reports of PCR and ELISA based detection of Pectobacterium used peel sample extract as a starting material or for enrichment of the bacteria (Bång, 1989; Hyman et al., 1997, 2000; Hélias et al., 1998; Pérombelon et al., 1998; De Boer, 2002). The result of the study by De Boer (2002) that suggested stolon end samples to be better than peel samples for estimating the prevalence of Pectobacterium is not consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A more reliable indication of seed health status is obtained by determining the level of seed tuber contamination using Eca‐specific diagnostics (Pérombelon et al ., 1997; Toth et al ., 1996). To enable the implementation of Eca diagnostics in a meaningful way, the relationship between the level of seed tuber contamination by Eca and progeny tuber contamination needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…These include selective plating on crystal violet pectate medium (CVP), immunological methods and the polymerase chain reaction (PCR), all of which differ in their sensitivity and ability to quantify Eca cells ( Toth et al . 1996 ; Pérombelon et al . 1998 ).…”
Section: Introductionmentioning
confidence: 99%